IMPROVING IMPREGNATION TECHNIQUES FOR FINE CONIFEROUS AND NON-CONIFEROUS WOOD - Kunickaya, Olga; Runova, Elena; Chzhan, Svetlana; Zhuk, Artem; Markov, Oleg; Garus, Ivan; Nikiforova, Valentina; Ivanov, Viktor (Journal of Applied Engineering Science, 2020)
Wood modification with the improvement of its physical and mechanical properties is a promising way to increase the commercial quality of the material and enhance its sustainable use. This article presents the results on developing a model for impregnation with water of fine coniferous and non-coniferous wood by centrifugal processing techniques. The mathematical modeling is based on Darcy’s law. According to the model representation, the impregnation rate of the wood assortment is proportional to the pressure ratio of the treating solution. The proportionality factor is a constant value that depends on the breed of wood. Performed comparative analysis revealed the perfect consistency of calculations made using the formula of a centrifugal model with the experimental data. According to the analysis of impregnation rate time dependencies, the main saturation of the treated sample with liquid (70%) occurs in 1/3 of the complete cycle time. Besides, the established model allows determining with high accuracy the impregnation time as a function of atmospheric pressure, rotational speed, and the ratio of assortment wood length to centrifuge platform radius for different wood breeds. Further studies are planned on evaluating the effect of different liquids viscosity on the kinetics of wood impregnation as well as determining the applicability of the proposed model.